Investigation of Toxicity in Textile Materials from Natural and Synthetic-based Polymers Utilizing Bioassay Performances - Elena Pekhtasheva; Elena Mastalygina; Irina Leonova; Sivasubramanian Palanisamy; Aravindhan Alagarsamy; Nadir Ayrilmis; Mika Sillanpää; Saleh A Al-Farraj (BioResources)
Assessing the toxicity of textile samples in terms of risks to human well-being and health is a significant issue. In this study, 11 textile materials were tested using two procedures: the sperm motility inhibition test using bull spermatozoa and the acute immobility test using Daphnia magna. A comparative analysis was carried out considering the advantages of each toxicity assessment method. The bull sperm test was shown to be less sensitive and more complicated to carry out than the Daphnia magna immobility test. In addition, the inclusion of both dyes and synthetic fibres significantly influenced textile toxicity, with aqueous extracts from dyed textiles showing higher toxicity levels when tested alongside undyed textiles. The toxicity index for dyed textiles ranged from 37% to 62% in the motility inhibition test, while the Daphnia magna test showed an acute immobility parameter of 100% with the uncontaminated control medium.